The elected representative as an intermediary between the group and the power (Psicologia USP, 2017)
The article examines the hypothesis that the democratic system as a model for organizing established groups has an intersubjective function of maintaining social bonds by transferring the discomfort of coexistence to the chosen representative, all without endowing the representative with absolute power. The representative therefore holds the taboo position, maintaining the narcissistic and omnipotent desire rejected by members. From the representative’s point of view, this means subjugating his/her ego ideal to group ideals in a movement contrary to that of the leader; as described by Freud in Group psychology and the analysis of the ego. This hypothesis was used to analyze the life story of a union representative and to depict his psychological suffering during his mandate and after leaving the union. Psychoanalysis and psychosociology are the primary underlying theories used in particular texts by S. Freud, R. Kaës, J. Barus-Michel and E. Enriquez.